Togo : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Modification of a Performance Criterion and Request for Extension of the Arrangement-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Togo. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Togo showed solid progress under the Extended Credit Facility (ECF)-supported economic program. Executive Directors appreciated its strong track record of policy, reform implementation, and commitment to sound reforms. In addition to maintaining macroeconomic stability, Togo has fully met all other requirements for the HIPC completion point. The Executive Board welcomed its achievement on completion of the fifth review under the ECF and granted extension of the arrangement under HIPC to create the financial space toward the acceleration of its reform agenda, economic development, and meeting the MDGs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet